2015
DOI: 10.1159/000441621
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase 2 as a Potential Mediator of Vascular Smooth Muscle Cell Migration and Chronic Vascular Remodeling in Hypertension

Abstract: For vascular remodeling in hypertension, it is essential that vascular smooth muscle cells (VSMCs) reshape in order to proliferate and migrate. The extracellular matrix (ECM) needs to be degraded to favor VSMC migration. Many proteases, including matrix metalloproteinases (MMPs), contribute to ECM proteolysis and VSMC migration. Bioactive peptides, hemodynamic forces and reactive oxygen-nitrogen species regulate MMP-2 expression and activity. Increased MMP-2 activity contributes to hypertension-induced maladap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
99
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 103 publications
(170 reference statements)
2
99
1
5
Order By: Relevance
“…Downstream effectors of oxidative stress in VSMCs include plasminogen activator inhibitor PAI-1 [16, 54] and the matrix metalloproteinases MMP2 and MMP9, also known as gelatinases [14-17, 55]. The increased PAI-1 expression, a regulator of VSMCs calcification [28, 56], is attenuated by Fibulin-3 during high phosphate conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Downstream effectors of oxidative stress in VSMCs include plasminogen activator inhibitor PAI-1 [16, 54] and the matrix metalloproteinases MMP2 and MMP9, also known as gelatinases [14-17, 55]. The increased PAI-1 expression, a regulator of VSMCs calcification [28, 56], is attenuated by Fibulin-3 during high phosphate conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, Fibulin-3 reduces systolic blood pressure and improves vascular health [10], at least in part, by reducing aortic oxidative stress [10-12] and expression of matrix gelatinases [10, 13]. In vascular smooth muscle cells (VSMCs), gelatinase expression and activity are stimulated by excessive oxidative stress [14-17]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, TNF‐β, which is upregulated in joint tissues after hemarthrosis in hemophilic mice, increases the activity of MMP‐2 and other MMPs that are well known to contribute to maladaptive vascular remodeling in hypertension. These enzymes degrade basement membranes, thereby facilitating migration and proliferation of vascular smooth muscle cells. It has been demonstrated that following joint bleeding, MMPs are overexpressed in joints of hemophilic mice, and basement membrane turnover is accelerated in hemophilic rat joints .…”
Section: Discussionmentioning
confidence: 99%
“…Reciprocal interaction between vascular cells and their ECM is pivotal in blood vessel formation and remodelling [1]. Hypertensive vascular remodelling is an adaptive response to changes in the blood-pressure-induced circumferential wall stress and blood-flow-induced wall shear stress, which result in the degradation and reorganization of the vascular ECM protein, such as collagen, elastin, proteoglycan and fibronectin [2, 3]. …”
Section: Introductionmentioning
confidence: 99%
“…The renin-angiotensin system plays a pivotal role in vascular remodelling: angiotensin II has some effects on vascular fibroblast proliferation, ECM protein production and adhesion to matrix proteins. The hypertrophic remodelling is associated with an increase in the arterial wall thickness characterized by collagen deposition and elastin degradation, it is also common in large arteries, such as the aorta, in chronic severe hypertension [2]. …”
Section: Introductionmentioning
confidence: 99%